Water in rechargeable multivalent‐ion batteries : an electrochemical Pandora's box - Manalastas, William, Jr. (2020)
Multivalent‐ion batteries built on water‐based electrolytes represent energy storage at suitable price points, competitive performance, and enhanced safety. However, to comply with modern energy‐density requirements, the battery must be reversible within an operating voltage window greater than 1.23 V or the electrochemical stability limits of free water. Taking advantage of its powerful solvation and catalytic activities, adding water to electrolyte preparations can unlock a wider gamut of liquid mixtures compared with strictly nonaqueous systems. However, a point‐by‐point sweep of all potential formulations is arduous and ineffective without some form of systematic rationalization. The present Review consolidates recent progress, pitfalls, limits, and insights critical to expediting aqueous electrolyte designs to boost multivalent‐ion battery outputs.